Deep Brain Stimulation of the Internal Globus Pallidus Improves Response Initiation and Proactive Inhibition in Patients With Parkinson’s Disease - Pan, Yixin; Wang, Linbin; Zhang, Yingying; Zhang, Chencheng; Qiu, Xian; Tan, Yuyan; Zhou, Haiyan; Sun, Bomin; Li, Dianyou (Frontiers in Psychology, 2018)
Background: Impulse control disorder is not uncommon in patients with Parkinson’s disease who are treated with dopamine replacement therapy and subthalamic deep brain stimulation (DBS). Internal globus pallidus (GPi) DBS is increasingly used, but its role in inhibitory control has rarely been explored. In this study, we evaluated the effect of GPi DBS on inhibitory control in PD patients. Methods: A stop-signal paradigm was used to test response initiation, proactive inhibition, and reactive inhibition. The subjects enrolled in the experiment were 27 patients with PD, of whom 13 had received only drug treatment and 14 had received bilateral GPi-DBS in addition to conventional medical treatment, and 15 healthy individuals. Results: Our results revealed that with GPi-DBS on, patients with PD showed significantly faster responses than the other groups in trials where it was certain that no stop signal would be presented. Proactive inhibition was significantly different in the surgical patients with GPi-DBS on versus when GPi-DBS was off, in surgical patients with GPi-DBS on versus drug-treated patients, and in healthy controls versus drug-treated patients. Correlation analyses revealed that when GPi-DBS was on, there was a statistically significant moderate positive relationship between proactive inhibition and dopaminergic medication. Conclusion: GPi-DBS may lead to an increase in response initiation speed and improve the dysfunctional proactive inhibitory control observed in PD patients. Our results may help us to understand the role of the GPi in cortical-basal ganglia (BG) circuits.